The problem of future users: how constructing the DNS shaped internet governance - Steven Malcic (Internet Policy Review, 2016)
Before the emergence of internet governance bodies like the Internet Corporation for Assigned Names and Numbers (ICANN), early network designers learned how to govern the internet in their work building the Domain Name System (DNS). Using original archival research, this article follows conversations among network designers in their daily struggle to keep the Advanced Research Project Agency Network (ARPANET) and early internet in working order. Drawing from social constructivism and path dependence theory, this history helps to conceive "internet governance" beyond its institutional focus, considering how the work of ordering the internet necessarily exceeds the parameters of governance authorities.
Keywords: 300; Internet governance; Internet history; Network design; Domain Name System (DNS); Path dependence